La Russie - un pays qui transcende l'Europe - Holenstein, Elmar (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
Elmar HOLEN STEIN, Eidgenössische Technische Hochschule Zürich : «Russia's Contribution to European Culture» In a paper written in 1944/45, Jakobson shows that the idea of national auto-determination is not a Western European concept, but an Eastern European one, of biblical inspiration. This idea is linked to another one : no world state has the right to hegemony. With such political ideas, Russia works as the go-between for a Byzantine philosophy. But Russia is not only, as an Eastern European country, an intermediary of Byzantine culture, but also, as a Eurasian country, a go-between of East Asian culture. According to Fernand Braudel, the civilizing role of Mongolia in Russia could be compared to the role played by Muslim Spain vis-a-vis Christian Spain. Trubetzkoy would probably have agreed with such a judgment, and would probably have sought evidence to back it up with.